Soil test crop response based phosphorus calibration study for bread wheat in Kofele District, West Arsi Zone Oromia, Ethiopia - Husien, Abdurahman; Firomsa, Tilahun; Abera, Tilahun (Journal of Scientific Agriculture, 2021)
Nowadays, a balanced fertilizer recommendation is of paramount importance in order to confirm the security and sustainably increase crop productivity for farmers and other stakeholders. Soil test crop response based phosphorus calibration study in two years (2017 and 2018) was done for bread wheat in kofele district with objectives to assess and evaluate yield response of bread wheat to phosphorus-fertilizer applications in soils that have initial high/medium/low levels of phosphorus on Eutric Vertisols. A composite soil samples collection were made in zigzag method from farmer’s land and analyzed for available P in order to identify the level of the required parameters in the soil to select farmland for actual experiment. Accordingly, phosphorus calibration study treatments include application of 0, 10,20,30,40 and 50 kg P ha-1 with recommended nitrogen 69 kg N ha-1 with RCBD design was used with two replications. The plot size of 5mx4m with a seed rate of 150 kg ha-1 and Ogolcho variety which had been recommended for the area was used. So that the result showed that phosphorus fertilizer application significantly affects yield and yield components of bread wheat. Similarly, phosphorous fertilizer application at different rates increased grain yield of bread wheat by 28 to 44% compared to the control. Furthermore, the study was revealed that phosphorus critical (Pc) point for bread wheat was 19, and phosphorus requirement factor was also 3.30. Therefore, future research should focus on verification of the result on farmland before disseminating the technology to the end-user.